Stock price forecast accuracy and recommendation profitability of financial magazines - Victor Tiberius; Laura Lisiecki (International Journal of Financial Studies, 2019)
In this study, we analyze the forecast accuracy and profitability of buy recommendations published in five major German financial magazines for private households based on fundamental analysis. The results show a high average forecast accuracy but with a very high standard deviation, which indicates poor forecast accuracy with regard to individual stocks. The recommendation profitability slightly exceeds the performance of the MSCI World index. Considering the involved risk, which is represented by a high standard deviation, the excess returns appear to be insufficient.
Keywords: G11; G17; 330; buy recommendations; financial magazines; forecast accuracy; MSCI World; recommendation profitability